Nilai-Nilai Pendidikan Humanis pada Tradisi Lokal Yasinan di Dusun Krasak dan Kecis Kecamatan Selomerto Kabupaten Wonosobo - Nanang Sudiyono; Ngarifin Shidiq; Robingun Suyud El Syam (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
Humanist values ​​in education have long been rooted in the religious traditions and local culture of Indonesian society, but field facts are needed to strengthen this argument. This research focuses on three objectives: (1) analyzing the humanist educational values ​​contained in the local yasinan tradition in the hamlets of Krasak and Kecis, Selomerto, Wonosobo; (2) knowing the implications of humanist education from the implementation of the local yasinan tradition in the hamlets of Krasak and Kecis, Selomerto, Wonosobo; (3) understanding the relevance of humanist education reflected in the implementation of the local yasinan tradition in the hamlets of Krasak and Kecis, Selomerto, Wonosobo to Islamic religious education. This thesis is the result of a field study in the hamlets of Krasak and Kecis, Selomerto sub-district, Wonosobo regency regarding the local yasinan tradition. Primary sources were obtained through observation, interviews and documentation, strengthened by other relevant secondary sources, then analyzed qualitatively descriptively through three stages: data reduction, data presentation, and drawing conclusions—verification. The results of the analysis and discussion show that: (1) The Yasinan tradition in the Krasak and Kecis hamlets, Selomerto District, Wonosobo Regency contains a number of humanist educational values, namely: solidarity and brotherhood, empathy and sympathy, mutual cooperation, tolerance, knowing each other, character and moral education, and social concern; (2) The main implications of humanist educational values ​​in the Yasinan tradition in the Krasak and Kecis hamlets, Selomerto District, Wonosobo Regency, include: strengthening social solidarity and togetherness, instilling the values ​​of empathy and care, and character building based on local values; (3) The Yasinan tradition in the Krasak and Kecis hamlets, Selomerto District, Wonosobo Regency has strong relevance to Islamic Religious Education because it is an effective medium for instilling humanist educational values, such as solidarity, empathy, and togetherness, which are in line with Islamic teachings on human relations (muamalah) and noble morals.